A ANTECIPAÇÃO DA PUBERDADE EM RATAS TRATADAS COM BISFENOL A ESTÁ RELACIONADA A ALTERAÇÕES NO PADRÃO DE EXPRESSÃO DA KISSPEPTINA - Lorenzett, Ariane Krause Padilha (2021)
The female reproductive system depends on the development of the hypothalamic-pituitary-ovarian axis (HHO). Puberty is an important period in which reactivation of endocrine pathways and changes in body physiology occur. Bisphenol A (BPA) is an estrogen compound, being considered a chemical endocrine disruptor, which is used in the production of plastics and epoxy resins, being the raw material for food packaging and several other products. The aim of this work was to evaluate the molecular mechanisms involved in the onset of puberty in Wistar rats exposed to doses below the reproductive BPA NOAEL (no observed adverse effect level). For this purpose, recently weaned Wistar rats were divided into 3 subgroups (pre-pubertal, puberty and post-pubertal), which were treated with 5 mg / kg BPA body weight from the postnatal day (PND) 22 to the PND 35, daily, by gavage. From the PND22, the evaluation of the progression of puberty started by finding the opening of the vaginal orifice. The rats were euthanized according to the three moments of their reproductive development: before, at puberty and after the discovery of puberty, and blood, hypothalamus, pituitary and ovaries were collected. MRNA expression was assessed by real-time quantitative PCR (RT-qPCR). In the hypothalamus, the following genes were evaluated: gonadotropin-releasing hormone (gnrh1), estradiol alpha receptor (Esr1), estradiol beta receptor (Esr2) and the kisspeptin peptide (kiss1). In the pituitary gland the expression of the gonadotropin releasing hormone receptor (Gnrhr), luteinizing hormone (lhb), follicle stimulating hormone (fshb), progesterone receptor (Pgr), Esr1 and Esr2 were evaluated. In the ovary, the mRNA expressions of the luteinizing hormone receptor (Lhr), follicle stimulating hormone receptor (Fshr), Esr2 and Pgr were analyzed. Serum measurements of LH and FSH were performed by chemiluminescence. The data were analyzed by two-way ANOVA and planned comparisons followed by Dunnet post-tests (reproductive development x control phase; reproductive development x treated phase) and Sidak (control x treated x reproductive development phase), Kruskal-Wallis followed Dunn's post-test (age at puberty) using the features of the GraphPad Prism 6 software (GraphPad Software Inc., San Diego, CA, USA) and Statistica 7.0 (Statsoft. Inc). Statistical difference was considered in all analyzes, when p <0.05. The serum levels of FSH and LH showed no significant difference. There were no changes in the pituitary gland with a significant difference. In the ovary, there was a difference in the Ers2 transcripts between the development phases (prepubertal, puberty and postpubertal) in the control group (p <0.05) and in the treated group (prepubertal, puberty and postpubertal) with (p <0.001). In the hypothalamus, there was a decrease in gnrh1 transcripts between the developmental stages of the post-pubertal age control group in relation to the pre-pubertal age (p <0.05). There was also an increase in kiss1 transcripts between the developmental stages of the treated group at age at puberty (p = 0.01) and at age after puberty (p <0.001) when compared to pre-puberty age. A difference between treatments is also observed in the hypothalamus, where there was an increase in the kiss1 transcripts in the treated group in relation to the control group, this in post-pubertal age (p <0.01). Esr2 transcripts border line changes (p = 0.07). These results show that the anticipation of puberty in rats exposed to BPA is related to changes in the expression of kisspeptin, which is related to the triggering of GnRH synthesis and secretion and to decreases in the expression of Esr2 in the ovary, which may be related to an desensitization of the receptor. Such changes demonstrate that exposures to BPA in doses below NOEAL can cause impairment of the female reproductive system, bringing consequences in adulthood.